PEMISAHAN PENYIDIKAN TINDAK PIDANA PENCUCIAN UANG (MONEY LAUNDERING) DARI TINDAK PIDANA KORUPSI SEBAGAI TINDAK PIDANA ASAL (PREDICATE CRIME) - Muhammad Junaidi; Bismar Nasution; Mahmud Mulyadi; Edi Yunara (USU LAW JOURNAL, 2018)
ABSTRACT   Investigation of money laundering crime and corruption as a criminal offense is very possible to be done separately or there is a separation of investigation. Therefore, it is necessary to examine the separation of investigation into money laundering crime with corruption as an offense. Factors that affect the separation of investigations in money laundering crime with corruption as an offense. Obstacles in separating the investigation of money laundering crime with corruption as a criminal act of origin and efforts to overcome the barriers of separating the investigation of money laundering crime with corruption as an offense.   Keywords: Separation, Corruption and Money Laundering Crime